The Influence of Hyper Reading on Learning Media Development - Ariani, Diana; Ardiansyah, Acep Ahmad; Zianadezdha3, Asfara; Khatulistiwa, Fairuz (Jurnal Pembelajaran Inovatif, 2023)
This research focuses on problems regarding the reading habits of the digital native generation, known as hyper reading, which influences the development of learning media. Because currently, the development of learning media pays little attention to the reading characteristics of its users. So, this research aims to determine the influence of hyper reading on the development and packaging of learning media. This study used descriptive qualitative method. One way to obtain this data is through literature studies, surveys and focus group discussions. The survey results found that the characteristics of hyper reading that are most often felt by users are filtering, skimming, pecking, imposing, and filming. There are two categories of learning media that are influenced by hyper reading, namely print and non-print media. The characteristics of hyper reading can influence the development of learning media that involves the reading process. The most significant influence is in the message design or packaging of learning media materials in accordance with the five characteristics of hyper reading, namely filtering, skimming, pecking, imposing and filming.